Preferred Rights The subscription of the shares of the capital increase of the shareholding companies and their disposal in the Egyptian Capital Law and its amendments - Abdel Gawad, Mahmoud Abdel Gawad Abdel Hadi (Journal of Economic, Administrative and Legal Sciences, 2018)
The priority right of subscription is the equity rights of the joint stock companies. The companies contributing to the determination of these rights resort to a financial and administrative balance. This was optional for the General Assembly، but successive amendments in Egyptian legislation have become binding in some cases to decide that each owner of the right of subscription may act in it or renounce it as he wishes.
Keywords: subscription; priority; capital increase; joint stock companies